PENGARUH CAPITAL EXPENDITURE, INVESTMENT OPPORTUNITIES, CEO TENURE TERHADAP CASH HOLDING PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA: THE EFFECT OF CAPITAL EXPENDITURE, INVESTMENT OPPORTUNITIES, CEO TENURE ON CASH HOLDING IN NON-FINANCIAL COMPANIES LISTED ON THE INDONESIAN SHARIA STOCK INDEX - Widia Ayu Permatasari; Gatot Nazir Ahmad; Destria Kurnianti (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
This study aims to determine the effect of Capital Expenditure (CAPEX), Investment Opportunities (Sales Growth), CEO Tenure (TN) on Cash Holding. The independent variables used in this study are Capital Expenditure, Investment Opportunities and CEO Tenure. The dependent variable used in this study is Cash Holding. The data source used in this study is secondary data in the form of the company's annual financial report. The population in this study are non-financial companies listed on the Indeks Saham Syariah Indonesia (ISSI) for the 2013-2017 period. The number of samples used in this study were 155 companies with observations for 5 years so that 775 objects of observation were selected. The sampling method used in this study was a purposive sampling technique. The model used in this study is panel data with a fixed effect model approach. The results obtained from this study are that Capital Expenditure has an effect on Cash Holding, Investment Opportunities have no effect on Cash Holding, and CEO Tenure has an effect on Cash Holding